Surgical fusion of early onset severe scoliosis increases survival in Rett syndrome: a cohort study. (11th December 2015) - Downs, Jenny; Torode, Ian; Wong, Kingsley; Ellaway, Carolyn; Elliott, Elizabeth J; Izatt, Maree T; Askin, Geoffrey N; Mcphee, Bruce I; Cundy, Peter; Leonard, Helen; ,
Abstract : Aim: Scoliosis is a common comorbidity in Rett syndrome and spinal fusion may be recommended if severe. We investigated the impact of spinal fusion on survival and risk of severe lower respiratory tract infection in Rett syndrome. Method: Data were ascertained from hospital medical records, the Australian Rett Syndrome Database, a longitudinal and population‐based registry, and from the Australian Institute of Health and Welfare National Death Index database. Cox regression and generalized estimating equation models were used to estimate the effects of spinal surgery on survival and severe respiratory infection respectively in 140 females who developed severe scoliosis (Cobb angle ≥45°) before adulthood. Results: After adjusting for mutation type and age of scoliosis onset, the rate of death was lower in the surgery group (hazard ratio [HR] 0.30, 95% confidence interval [CI] 0.12–0.74; p =0.009) compared to those without surgery. Rate of death was particularly reduced for those with early onset scoliosis (HR 0.17, 95% CI 0.06–0.52; p =0.002). There was some evidence to suggest that spinal fusion was associated with a reduction in risk of severe respiratory infection among those with early onset scoliosis (risk ratio 0.41, 95% CI 0.16–1.03; p =0.06). Interpretation: With appropriate cautions, spinal fusion confers an advantage to life expectancy in Rett syndrome. What this paper adds: Survival was better in those with severe scoliosis who had surgical compared to conservative management. This was more marked in those with earlier onset scoliosis where possible protective effects on respiratory health were also observed. Our findings provide a framework of evidence from which clinicians and families can make their individual decisions. Our methods demonstrate the value of well‐managed databases for the investigation of rare disorders. This article is commented on by Humphreys on pages538–539 of this issue.